An Uncommon Ammunition Case: Interpreting “Transitional” Textiles and Social Worlds in Nineteenth-Century Tlingit Alaska - Allen, Laura J. (DigitalCommons@University of Nebraska - Lincoln, 2020)
Overlooked objects in museum collections can reveal complex social relationships behind well-known textile forms. A tattered woven case for ammunition cartridges, collected in southern Alaska in the late nineteenth century, presents such an opportunity. Part of the vast Tlingit collection at the American Museum of Natural History, the ammunition bag has been little documented and displayed compared to other highly esteemed indigenous naaxein or Chilkat weavings of the region. The piece is unusual in that the maker combined two weaving styles—not only figural motifs characteristic of Chilkat weaving, but also geometric patterns reminiscent of its stylistic and technical precursor called Raven’s Tail, of which few historic pieces remain. In this paper, I analyze the bag’s design, manufacture, and use, and contextualize its attributes using comparative objects, ethnohistorical sources, and contemporary dialogues with weavers and others from the Northwest Coast. I suggest that this case’s specific patterns, construction, and symbolism attest to major transitions (as well as continuities) occurring within Tlingit communities during the nineteenth century, a period of intense colonial pressure. These transitions include gender shifts in textile design, an increase in militaristic symbolism in ceremonial potlatch regalia, and adaptations in the look and socioeconomic roles of dress, textiles, and basketry. I interpret this special case as a connective object, linking shifting modes of expression and social relations during a time of transformation for indigenous groups of the Northwest Coast.